2002
DOI: 10.1016/s0006-3223(01)01301-4
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental patterns of visual P3b in association with familial risk for alcohol dependence and childhood diagnosis

Abstract: Background-The P3b component of the event-related potential (ERP) has frequently been reported to be reduced in children and adolescents at high risk for developing alcoholism relative to control children and adolescents without familial loading for alcohol dependence. P300 amplitude changes during development for all children. Previously it has been shown that highrisk offspring display a pattern in which the amplitude is lower at age 8 with a smaller rate of change during adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 60 publications
6
48
1
Order By: Relevance
“…Whereas this pattern was clearly evident in boys, girls demonstrated small P300 components only in the presence of a diagnosed childhood disorder. These results were confirmed in a larger study by Hill and Shen (2002).…”
Section: High-risk Studiessupporting
confidence: 74%
“…Whereas this pattern was clearly evident in boys, girls demonstrated small P300 components only in the presence of a diagnosed childhood disorder. These results were confirmed in a larger study by Hill and Shen (2002).…”
Section: High-risk Studiessupporting
confidence: 74%
“…This finding appears to be most strongly related to age (younger children/adolescents in contrast to adults), gender (boys have lower P300 than girls) and the density of alcoholism cases within the family. Our longitudinal follow-up of the same children at yearly intervals shows that developmental trajectories of P300 amplitude differ between risk groups [Hill et al, 1999c] and variation in trajectory pattern may be associated with risk for developing a childhood or adolescent psychiatric disorder [Hill and Shen, 2002]. An association between P300 amplitude at age 10 and later development of alcohol problems was seen in 18 year olds in our laboratory [Hill et al, 1995c].…”
Section: Discussionmentioning
confidence: 66%
“…Subsequent studies revealed that reduced P300 amplitude was associated not just with active symptoms, but also with risk for the development of alcohol problems. For example, children and adolescents with a paternal history of alcoholism show reliably reduced P300 compared with family-negative controls (Begleiter, Porjesz, Bihari, & Kissin, 1984;Elmasian, Neville, Woods, Schuckit, & Bloom, 1982;Hill & Shen, 2002; for review, see Address reprint requests to: Christopher J. Patrick, Department of Psychology, University of Minnesota, Elliott Hall, 75 East River Road, Minneapolis, MN 55455, USA; E-mail: cpatrick@tc.umn.edu. 1 The term P3b is sometimes used for this frequency-sensitive component, to distinguish it from the "P3a" or "novelty P3," maximal at fronto-central sites, which follows the occurrence of an unexpected rare nontarget stimulus (Coles & Rugg, 1995).…”
Section: P300; Externalizing; Psychopathologymentioning
confidence: 99%